Diseño de un plan de negocio para la creación de una empresa fabricante de espacios locativos y residenciales a base de containers en la ciudad de Santa Marta (2022)
The construction and real estate sector has shown a growing trend in recent years, which poses an optimal outlook by virtue of the development of economic activity and the market to which this business proposal is aimed. For this reason, it is consistent to state that there is a growing sector that is increasing in terms of demand and what remains without many innovative options that make up for the deficit reflected in the acquisition of spaces for the population that emerges with the desire to supply a basic need but that has few possibilities of owning a real estate property due to lack of economic resources. In this sense, the current business proposal has specifications that provide a solution to the problem raised and respond, in turn, to issues of cost reduction, sustainable content and social potential for the application of construction systems; that is why the clear objective of the model is to provide a real estate product, using reusable containers and with ecofriendly characteristics, to all the residents of the city of Santa Marta and Colombia who are looking for an economic and sustainable alternative. The type of research to be used for the structuring of this business proposal is based on a dual component that unifies the quantitative and qualitative method, with a line of institutional innovation research in organizations.